Peningkatan Pemahaman Penjumlahan Bersusun Dengan Teknik Menyimpan Siswa Tunagrahita Ringan Melalui Alat Rak Kantong Nilai Bilangan - Febri Efi Haryani; Alpian Alpian (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The research problem is that students are mildly mentally retarded and have poor understanding of the material for calculating multilevel additions. The aim of this research is to improve understanding of compound addition material by storing techniques through the use of number value racks. Class IV students at the Toboali State Special School who have mild intellectual disabilities will benefit from a better understanding of the concept of multiple addition operations. This type of research is called Classroom Action Research (CAR). This research was carried out in two cycles, each cycle being carried out in three meetings. Each cycle has four interrelated phases: observation, reflection, action implementation, planning phase, and reflection. The research subjects were four fourth grade Toboali State Special School students with mild intellectual disabilities. Data was collected through test and observation methods. Quantitative analysis was carried out on the data, and a table was presented showing student learning outcomes. Based on the results of research carried out in cycle I and cycle II, it shows that the use of number value racks can improve students' understanding of the material of addition in layers using storing techniques.